Mycobacterium tuberculosis dysregulates MMP/TIMP balance to drive rapid cavitation and unrestrained bacterial proliferation. Issue 3 (6th October 2014) - Kübler, André; Luna, Brian; Larsson, Christer; Ammerman, Nicole C; Andrade, Bruno B; Orandle, Marlene; Bock, Kevin W; Xu, Ziyue; Bagci, Ulas; Molura, Daniel J; Marshall, John; Burns, Jay; et al.
Abstract Active tuberculosis (TB) often presents with advanced pulmonary disease, including irreversible lung damage and cavities. Cavitary pathology contributes to antibiotic failure, transmission, morbidity and mortality. Matrix metalloproteinases (MMPs), in particular MMP‐1, are implicated in TB pathogenesis. We explored the mechanisms relating MMP/TIMP imbalance to cavity formation in a modified rabbit model of cavitary TB. Our model resulted in consistent progression of consolidation to human‐like cavities (100% by day 28), with resultant bacillary burdens (>107 CFU/g) far greater than those found in matched granulomatous tissue (105 CFU/g). Using a novel, breath‐hold computed tomography (CT) scanning and image analysis protocol, we showed that cavities developed rapidly from areas of densely consolidated tissue. Radiological change correlated with a decrease in functional lung tissue, as estimated by changes in lung density during controlled pulmonary expansion (R2 = 0.6356, p < 0.0001). We demonstrated that the expression of interstitial collagenase (MMP‐1) was specifically greater in cavitary compared to granulomatous lesions (p < 0.01), and that TIMP‐3 significantly decreased at the cavity surface. Our findings demonstrated that an MMP‐1/TIMP imbalance is associated with the progression of consolidated regions to cavities containing very high bacterial burdens. Our model provided mechanistic insight, correlating with human disease at the pathological, microbiological and molecular levels. It also provided a strategy to investigate therapeutics in the context of complex TB pathology. We used these findings to predict a MMP/TIMP balance in active TB and confirmed this in human plasma, revealing the potential of MMP/TIMP levels as key components of a diagnostic matrix aimed at distinguishing active from latent TB (PPV = 92.9%, 95% CI 66.1–99.8%, NPV = 85.6%; 95% CI 77.0–91.9%). Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd